Trends of anthropogenic CO2 along 20º W in the Iberian Basin - Fajar, NM; Pardo, PC; Carracedo, L; Vazquez-Rodriguez, M; Rios, AF; Perez, FF (2012)
The carbon system in the water masses of the Iberian Basin (North Atlantic Ocean) has been affected over the last two decades by the increase in anthropogenic CO 2 (Cant). In order to study the storage of Cant in the Iberian Basin, variables of the carbonic system (i.e., pH, total inorganic carbon, and total alkalinity), among others, were measured during the CAIBOX cruise conducted between July and August 2009 within the framework of the CAIBEX project (Shelf-Ocean Exchanges in the Canary-Iberian Large Marine Ecosystem). The storage of Cant was estimated using two different back-calculation techniques (i.e., the ϕCºT and TrOCA methods) and for six layers of the water column corresponding to the approximate locations of the characteristic water masses of the region and the mixed layers. For the whole water column and for the year 2009 the Cant storage values determined by the ϕCºT and TrOCA methods were 88.1 ± 3.8 and 93.7 ± 3.7 molC m–2, respectively. Moreover, the Cant storage rate from 1993 to 2009 was also estimated considering data from three additional cruises (OACES 1993, CHAOS 1998, and OACES 2003). The Cant storage rates were 1.41 ± 0.25 and 1.67 ± 0.13 molC m–2 yr–1 with the ϕCºT and TrOCA methods, respectively. An increase in anthropogenic CO 2 uptake by the ocean can be seen when compared with previous published results. Between the periods 1977–1997 and 1993–2009, the Cant concentration increased around 28–49% in the first 2000 m.